Neutrophil-lymphocyte ratio, pain perception, and disease activity score may serve as important predictive markers for sustained remission in rheumatoid arthritis - S. Chandrashekara; A. Rajendran; A. Bai Jaganath; R. Krishnamurthy (PAGEPress Publications, 2016)
The implementation of new treatment strategies based on current recommendations has enabled a greater number of patients with rheumatoid arthritis (RA) to achieve remission. However, there are no definite predictors of sustained remission. Moreover, the absence of clear consensus on the time of withdrawal or reduction of treatment further adds to the treatment burden. This pilot study was intended to evaluate the prognostic potential of various RA-related parameters. All the enrolled subjects (n=124) were clinically evaluated on the basis of various parameters including age, gender, duration of illness before the initiation of disease-modifying anti-rheumatic drugs, tender and swollen joints (28 joints), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), hemoglobin percentage, lymphocyte count, total white-blood cell counts, and neutrophil to lymphocyte ratio (NLR). Student's t-test and discriminant function analysis were performed. The specificity of all parameters and their best possible cut-off to predict relapse were calculated using the receiver operating characteristic (ROC) analysis. A significant difference in terms of pain perception, NLR, tendency to have a significant tender joint count and absolute lymphocyte counts was identified between the patients in sustained remission and those in relapse. The ROC analysis indicated that NLR was consistent in predicting remission. CRP, ESR, and/or disease activity score may not be very effective in differentiating patients with sustainable remission/low disease activity. NLR along with patient's perception of pain may assist in predicting sustained remission.